2018
DOI: 10.1007/s10072-018-3463-6
|View full text |Cite
|
Sign up to set email alerts
|

The initial glycemic variability is associated with early neurological deterioration in diabetic patients with acute ischemic stroke

Abstract: The association between glycemic variability and early neurological deterioration (END) in acute ischemic stroke remains unclear. This study attempted to explore whether initial glycemic variability increases END in diabetic patients with acute ischemic stroke. We enrolled type 2 diabetic patients undergoing acute ischemic stroke from November 2015 to November 2016. A total of 336 patients within 72 h from stroke onset were included. The serum glucose levels were checked four times per day during the initial 3… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
29
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(33 citation statements)
references
References 32 publications
1
29
1
Order By: Relevance
“…A large number of studies have confirmed that END is an independent risk factor for poor prognosis in stroke patients (Hui et al., 2018; Simonsen et al., 2016; You et al., 2019). Consequently, predictive factors for END are also of great interest.…”
Section: Discussionmentioning
confidence: 94%
“…A large number of studies have confirmed that END is an independent risk factor for poor prognosis in stroke patients (Hui et al., 2018; Simonsen et al., 2016; You et al., 2019). Consequently, predictive factors for END are also of great interest.…”
Section: Discussionmentioning
confidence: 94%
“…Several recent clinical studies suggested that glycemic variability could be associated with the development and severity of coronary artery disease in patients with normal glucose tolerance, prediabetes, and diabetes [23-25]. A previous study also reported that glycemic variability after stroke onset could be associated with END in diabetic patients only [26]. However, evidence investigating the different pathological mechanisms of glycemic variability between prediabetic and diabetic patients has yet to be performed.…”
Section: Discussionmentioning
confidence: 99%
“…In addition to hypoglycemia and hyperglycemia, glycemic variability (GV) was considered as another important component of dysglycemia (43). It was reported that GV within the initial 3 hospital days was associated with increased risk for END in diabetic patients with AIS (44). Although the mechanism for the occurrence of GV in patients with AIS is not clear, GV was strongly associated with infarct volume, severity of symptoms, and stroke outcomes (45,46).…”
Section: Association Between Hyperglycemia End and Sexmentioning
confidence: 99%